Two new 14, 15-secopregnane-type steroidal glycosides from the roots of Cynanchum limprichtii. Issue 3 (1st February 2018) - Liu, Jia-chuan; Yu, Li-li; Chen, Shao-fei; Lu, Xiao-jie; Zhao, Dan; Wang, Hai-feng; Chen, Gang; Pei, Yue-hu
Abstract: Two new steroidal glycosides1 and2, along with three known ones (3 –5 ), were isolated from the 95% ethanol extract of the roots of Cynanchum limprichtii Schltr. The structure of the new compounds was elucidated as 3-O- α -L-diginopyranosyl-(1→4)- β -D-digitoxopyranosyl-(1→4)- β -D-cymaropyranosyl-(1→4)- β -D-thevetopyranosyl-14, 16:15, 20:18, 20-triepoxy-14, 15-secopregn-4, 6, 8 (14)-triene (1 ) and 3-O- α -L-cymaropyranosyl-(1→4)- β -D-digitoxopyranosyl- (1→4)- β -D-3-demethyl-2-deoxythevetopyranosyl-14, 16: 15, 20: 8, 20-triepoxy-14, 15-secopregn-5, 8 (14)-diene (2 ) on the basis of spectroscopic analysis together with acidic hydrolysis. All compounds showed cytotoxic activity against the human cancer cell line HL60, with IC50 values of 55.36, 65.41, 17.88, 17.68 and 33.5 μM, respectively. While, only compound3 showed cytotoxicity against the Caco-2 cell line, with an IC50 value of 67.47 μM. Abstract :